Molecular docking test on plants fruit pomegranate red (Punica granatum L.) as disease inhibitor agent heart (cardiovascular) - Mumtaz, Raydina; Idami, Zahratul (Institute of Computer Science (IOCS), 2025)
Work fatigue is one of the occupational health and safety problems. This study was to evaluate the potential of active compounds from pomegranate plants (Punica granatum L.) as heart disease inhibitor agents through a Molecular docking approach. The method used involved 3D structural analysis of four active compounds – Quercetin, Caffeic acid, Ellagic acid, and Phenol – in this plant which were downloaded from PubChem and processed using Swiss Target Prediction, Super Prediction, PyMol, Pyrx software. The interaction between compounds and biological targets in this case Clopidogrel, was studied to determine binding energy, binding affinity and stability. The results showed the Ellagic acid and Quercetin had significant interaction with the lowest binding energy of -7.8 kcal/mol and -8.7 kcal/mol and the lowest RMSD value of 0 (Å) so that this can be said to have good interaction stability with the protein target. The 3D molecular structure of these two compounds also shows the presence of hydrogen bonds and effective interactions with amino acids as well as low toxicity and favorable affinity energy. Based on these results, Ellagic acid and Quercetin were identified as potential candidates in the development of drugs to treat heart disease (cardiovascular). This study is expected to review the potential of active compounds in pomegranates through the insilico method, which can support the development of natural alternatives, in accordance with herbal-based prevention efforts that are increasingly in demand by the community.